Observation of Omni Scale of Perceived Exertion during Fire Suppression Training. Issue 1 (August 2014) - Goss, Fredric L.; Robertson, Robert J.; Deldin, Anthony; Gibbs, Bethany Barone; Hostler, David
Ratings of perceived exertion in 66 firefighters before, during, and immediately after performing 20min. of fire suppression training were self-reported by the participants using the OMNI Walk-Run Scale and also recorded by a trained observer. The observer used the same definition of perceived exertion, instructions, and high and low anchoring procedures as the participants. Self-reported and observed ratings of perceived exertion did not differ before or during fire suppression training. Significant differences were noted between the self-reported and observed ratings immediately after fire suppression training. These findings support the use of direct observation to provide estimates of ratings of perceived exertion during fire suppression training.